(untitled) (Revista Contexto & Educação, 2021)
ABSTRACT: This article discusses the work-training relationship of social educators who work in the urban peripheries of Porto Alegre - RS. We present the categories popular educator and social educator and about the educational spaces of Non-School Education. The categories are contextualized historically-politically, making use of participant research. In addition, we stress the importance of social movements in the perspective of Popular Education, articulating the themes of education and Social Work. Keywords: Popular education and university. Non-School Education. Social Educators.